2020
DOI: 10.2147/cmar.s237073
|View full text |Cite
|
Sign up to set email alerts
|

<p>Parity as a Prognostic Factor in Patients with Advanced-Stage Epithelial Ovarian Cancer</p>

Abstract: This study aimed to determine the prognostic factors influencing the overall survival (OS) of Iranian women with epithelial ovarian cancer (EOC). Methods: Information about newly diagnosed patients with confirmed EOC at Motahari Clinic, Shiraz, Iran, from January 1, 2001, to December 31, 2016, was retrospectively reviewed and analyzed. Cox-adjusted proportional hazards (PH) and stratified Cox (SC) models were used to determine the potential prognostic factors. Results: The mean (±SD) age at the diagnosis of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
8
1
1
Order By: Relevance
“…A study conducted on EOC patients indicated that more than one parity improved OS in ASEOC patients 3 . However, the results of the current study did not show any relationship between the CDFS of EOC women and their parity.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…A study conducted on EOC patients indicated that more than one parity improved OS in ASEOC patients 3 . However, the results of the current study did not show any relationship between the CDFS of EOC women and their parity.…”
Section: Discussioncontrasting
confidence: 95%
“…The most common type of OC is epithelial ovarian cancer (EOC) which is the most lethal gynecologic malignancy in adult women 1 . The estimated overall 5‐year survival rate for early‐stage epithelial ovarian cancer patients (ESEOC: stages I and II) and patients with advanced‐stage epithelial ovarian cancer (ASEOC: stages III and IV) varies between 55% and 92% and 18% and 30%, respectively 2,3 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations